Lactic acid fermentation in the development of a seaweed sauerkraut‐style product: Microbiological, physicochemical, and sensory evaluation. Issue 2 (22nd January 2021) - Skonberg, D.I.; Fader, S.; Perkins, L.B.; Perry, J.J.
Abstract : Abstract: Consumption of nutrient‐rich seaweeds and fermented nondairy foods represent fast growing trends among health‐minded consumers. Assessment of lacto‐fermented seaweed was performed to address these trends, and to offer shelf‐life extension and product diversification for fresh kelps. The objectives were to evaluate the effects of kelp species and inclusion level on fermentation kinetics, physicochemical quality, safety, shelf‐life, and consumer acceptability of a seaweed sauerkraut‐style product. Six formulations with different inclusion levels (25, 50, and 75%) of shredded kelp (sugar kelp, SK or winged kelp, WK) were mixed with cabbage, 2% salt, and inoculated with Lactobacillus plantarum (approximately 10 6 CFU/g) and Leuconostoc mesenteroides (approximately 10 1 CFU/g). Products were processed in triplicate, fermented until a target pH of ≤4.6 was achieved, and sampled periodically for 60 days. Kelp species and inclusion level significantly affected most variables tested. The most rapid fermentation (3 days), as evidenced by pH decrease, lactic acid bacteria counts, and lactic acid levels, was noted in WK formulations. Some SK formulations took up to 14 days to achieve the target pH, and coliforms persisted to a greater extent in the SK formulations. Higher levels of kelp decreased the fermentation rate and concentration of fermentable sugars in the brine, but increased the total phenolic content and antioxidant activity of the sauerkrauts. Despite differences in instrumental color ( L * a * b * ) and texture (shear force) among formulations, overall liking as rated by a consumer panel was not significantly affected by species or inclusion level. Results support the use of lacto‐fermentation in the production of refrigeration‐stable seaweed sauerkraut‐style product. Practical Application: Health‐conscious consumers are becoming increasingly interested in plant‐based diets and fermented foods, and the development of novel seaweed sauerkraut‐style products can help to meet these needs. This study demonstrated the successful production of a sauerkraut‐style product formulated with up to 50% farm‐raised kelp. Physical, chemical, microbiological, and consumer acceptability testing established lactic acid fermentation as a viable method for shelf life extension and value addition of fresh kelps. These results provide science‐based information on an alternative processing method for cultivated seaweeds and can assist the industry in product diversification efforts.